THU0612 Providing healthcare for the poorest in east india – a report from a charity initiative, shakuntala hospital. (15th June 2017) - Brahe, CH; Rydholm, U; Pikwer, M; Schreiber, K; Ståhl-Hallengren, C; Bylander, B; Dash, R
Abstract : Background: The region of Odisha in India has a population of over 40 million people and 45% are living in poverty. Approximately one percent of the population is affected by inflammatory rheumatoid diseases. In order to provide early diagnosis and adequate treatment initiation to prevent long term disability, patients require easily accessible basic health care and rheumatologists. Accessible and affordable health care for patients with inflammatory diseases may not only improve disease diagnosis and management, but also improve their quality of life significantly Objectives: The aim of our abstract is: 1) To raise awareness of the need of support for common rheumatoid diseases in the developing world 2) To present Shakuntala Hospital as an example of a successful charity initiative Methods: The Indo-Swedish Rheumatology Foundation (ISRF) is an association of physicians whose main aim is to raise awareness, fundraise and to provide health care for patients suffering from inflammatory arthropathies. In order to bridge the gap between our advanced level of knowledge and treatment options in the western world and patients suffering from rheumatologic diseases in the Indian state Odisha we have established this unique association. ISRF, including Shakuntala Hospital, was founded in 2013 and has so far not only provided health care through diagnostic and treatment support, but also ensured patient education and physiotherapy. Health camps are organized in the peripheral communities in order to screen, diagnose and initiate first line treatment and refer these patients for follow-up care to Shakuntala Hospital for further treatments with disease modifying antirheumatic drugs (DMARD), disease monitoring and physiotherapy. Shakuntala Hospital is an example of a non-profit hospital with the aim to provide health care amongst the poorest areas in India. Results: We have so far registered over 2, 000 patients under our care, which includes patients registered in Shakuntala Hospital and in our peripheral care health camps. So far we have established outpatient care for patients with inflammatory arthritis in the districts of Balasore, Maurbhanja, Bhddark, Keonjhar, Jajpur districts of Odisa and Mednapur district of West Bengal and raised more than 32.000 Euro by ISRF from fundraising initiatives. Inspired by a Swedish model our osteoarthritis (OA) school was founded in October 2016 providing 6 week training courses with the main focusing on patients with knee OA. Furthermore, ISRF has increased awareness of skeletal fluorosis and provide a comprehensive focus with cleaning of drink water in co-operation with the Royal Technical High School in Stockholm. Conclusions: Shakuntala Hospital is an example of a successful charity initiative in order to provide healthcare for the poorest patients in East India. Awareness needs to be risen in order to further foster future support for Shakuntala Hospital. References: http://www.shakuntalahospital.com/ . Disclosure of Interest: None declared